Genetic factors associated with fibromyalgia: a narrative review - Merino, Amanda Susin (2022)
Fibromyalgia is a rheumatic disorder whose main symptom is chronic generalized pain accompanied by a set of symptoms such as sleep disturbance, depression, and chronic fatigue, among others. Its pathophysiology is complex, of multifactorial origin, including the influence of genetic factors. It has been shown that individuals with fibromyalgia show a pattern of family aggregation and that the probability of an individual developing this condition is about 50% attributed to genetic factors. In this sense, the present article aims to carry out a narrative review of the literature on the genetic aspects of fibromyalgia in its development and severity of symptoms. To this end, searches were carried out in PubMed and Scopus databases, using specific descriptors: “fibromyalgia” and “polymorphism”. Polymorphisms that influence pain modulation, such as those that occur in genes of the monoaminergic pathway or of catecholamine metabolism, are frequently found in studies of association with fibromyalgia. However, other target genes have emerged, related to the pathways responsible for the mechanisms of the most diverse symptoms that can affect these patients, such as neuroplasticity, neurotransmission, inflammation, vascularization, oxidative stress, cell cycle, among others.